1996
DOI: 10.1203/00006450-199605000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy and Safety of Pravastatin in 72 Children with Familial Hypercholesterolemia

Abstract: The safety, tolerability, and efficacy of a 12-wk treatment with pravastatin, 5, 10, and 20 mg/d, was evaluated in 72 children with heterozygous familial hypercholesterolemia (FH) in a double-blind, randomized and placebo-controlled study. The results show that pravastatin was well tolerated and that adverse events were mild and equally distributed among the three treatment groups. Plasma total and LDL cholesterol levels were significantly reduced in all pravastatin treatment groups, in comparison with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
3
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 17 publications
3
81
3
1
Order By: Relevance
“…Only nine of the 36 patients in our study had initial baseline LDL cholesterol levels that would be decreased to below 4.1 mM/L if a 25% reduction could be achieved. In addition, the lesser degree of LDL lowering observed with pravastatin in our study compared with that reported by Knipscheer et al (5) probably represents the higher initial LDL levels in our population, and the effects of diminished compliance probably attributable to the concomitant use of colestipol. Hennermann et al (26) studied the effects of diet and drug therapy in 71 children with familial hypercholesterolemia, and although noting significant effectiveness, the vast majority continued to have important hyperlipidemia.…”
Section: Discussioncontrasting
confidence: 55%
“…Only nine of the 36 patients in our study had initial baseline LDL cholesterol levels that would be decreased to below 4.1 mM/L if a 25% reduction could be achieved. In addition, the lesser degree of LDL lowering observed with pravastatin in our study compared with that reported by Knipscheer et al (5) probably represents the higher initial LDL levels in our population, and the effects of diminished compliance probably attributable to the concomitant use of colestipol. Hennermann et al (26) studied the effects of diet and drug therapy in 71 children with familial hypercholesterolemia, and although noting significant effectiveness, the vast majority continued to have important hyperlipidemia.…”
Section: Discussioncontrasting
confidence: 55%
“…11,17,19,21 One study showed less patients with adverse events in the statin-treated group, 17 whereas the others did not find a significant difference in the occurrence of adverse events. Analysis of the pooled data revealed no increased risk of an adverse event when receiving statin therapy, as shown by a relative risk (RR) of 0.99 (95% CI: 0.79 to 1.25; Table 3).…”
Section: Safetymentioning
confidence: 99%
“…11,17,20,21 Discontinuations varied from 0% 17 to 9% 20 in the statin groups and 0% 17 to 25% 20 in the placebo groups ( Table 1).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[60][61][62][63][64][65][66][67] Although these studies have generally been short-term, they have shown statins to be safe and effective in lowering cholesterol concentrations. More recent studies have included measures of vascular structure and function.…”
Section: -Hydroxy-3-methyl-glutaryl Coenzyme a Reductase Inhibitors mentioning
confidence: 99%